2020
DOI: 10.3390/brainsci10120986
|View full text |Cite
|
Sign up to set email alerts
|

One Multilocus Genomic Variation Is Responsible for a Severe Charcot–Marie–Tooth Axonal Form

Abstract: Charcot–Marie–Tooth (CMT) disease is a heterogeneous group of inherited disorders affecting the peripheral nervous system, with a prevalence of 1/2500. So far, mutations in more than 80 genes have been identified causing either demyelinating forms (CMT1) or axonal forms (CMT2). Consequentially, the genotype–phenotype correlation is not always easy to assess. Diagnosis could require multiple analysis before the correct causative mutation is detected. Moreover, it seems that approximately 5% of overall diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…This could explain the dysregulation of some genes in favor of others, explaining the development of a particular phenotype. Moreover, CMT2Z disease may be part of multilocus genetic pathologies (Miressi et al, 2020). In this study, the authors demonstrated that a combination of multiple genomic mutations is responsible for various severities in intra-familial members.…”
Section: Given Mutations Can Induce Different Phenotypesmentioning
confidence: 78%
“…This could explain the dysregulation of some genes in favor of others, explaining the development of a particular phenotype. Moreover, CMT2Z disease may be part of multilocus genetic pathologies (Miressi et al, 2020). In this study, the authors demonstrated that a combination of multiple genomic mutations is responsible for various severities in intra-familial members.…”
Section: Given Mutations Can Induce Different Phenotypesmentioning
confidence: 78%
“…This approach is already in place for other rare mendelian diseases such as Charcot-Marie-Tooth disease and others. [42][43][44][45]…”
Section: Discussionmentioning
confidence: 99%
“…A genome wide screen in ARSACS patients, aggregated based on phenotypic similarities, may provide a more complete genetic view of the disease. This approach is already in place for other rare Mendelian diseases, such as CMTs and others [42][43][44][45]. .…”
mentioning
confidence: 99%
“…Meanwhile, combinations of multiple variants are rarely described. Nevertheless, in a family with CMT, the conditions of the mother and daughter were characterized by axonal damage, and were associated with MORC21, MFN2, and AARS1 variants [ 44 ]. MFN2 is a member of the mitochondrial transmembrane protein family, which is widely expressed by eukaryotic cells and plays an important role in mitochondrial fusion and division-controlled mitochondrial dynamic remodelling [ 45 ].…”
Section: Application Of Next-generation Sequencing In Neurogenetic Diseasesmentioning
confidence: 99%
“…MORC2, in combination with the MFN2 variant, result in more severe phenotypes and complex clinical symptoms. The AARS1 variant was also found in healthy members of the family, suggesting it was not an independent risk factor [ 44 ]. However, the authors were unable to conclusively determine whether the AARS1 variant worsens CMT based on the presence of other causal mutations.…”
Section: Application Of Next-generation Sequencing In Neurogenetic Diseasesmentioning
confidence: 99%